Project to Develop a Geothermal System to Generate Electricity in Peru - Cordova, Elfry Vilcapoma; Aquino, Lizbeth Torres; Cordova, Enrique Vilcapoma; Hinostroza, Steve Camargo (International Journal of Energy Economics and Policy, 2022)
The use of renewable energy has been very important in recent decades for conserving nature, conserving its natural resources, and reducing environmental impacts. According to the ONU in 2019, greenhouse gases increased from 123% to 147% in the atmosphere, so one of the best alternatives that will help preserve our nature is geothermal energy, helping not only to take care of the environment but also to generate electricity, since in several countries the main problem is the lack of electricity, because it is essential for our daily tasks. This article presents it as a natural resource of our ecosystem that must be used to the maximum for electricity generation. For this, we will announce the most suitable places, for an optimal design. It will show different places in Peru that have the features, where you can implement a geothermal system. Tacna is the most relevant place with a lot of geothermal energy, and this was the place chosen for the geothermal system. It is therefore essential to exploit energy that is not exhausted, thereby increasing the use of new clean energy sources.